Atmospheric chemistry and physics : - Seinfeld, John H. (John Wiley &sons, 1998)
This fully revised and expanded version of John H. Seinfeld's successful Atmospheric Chemistry and Physics of Air Pollution provides a rigorous, comprehensive treatment of the chemistry of the atmosphere. With new chapters on such important topics as cloud physics, nucleation, and wet deposition, this book offers a truly up-to-date examination of atmospheric chemistry today